Stress biology of cyanobacteria : molecular mechanisms to cellular responses - Srivastava, Ashish Kumar.; Rai, A. N. 1944-; Neilan, Brett A. (Taylor & Francis, 2013)
"This reference is a compilation of holistic responses of cyanobacteria ranging from ecology and physiology to modem aspects of molecular biology and biochemistry. It presents research in cyanobacterial stress biologies, from classical to the most modern, and provides a holistic view of cyanobacterial bioenergetics under different abiotic stresses. Authors focus on topics ranging from evolution, ecophysiology, biochemistry, and molecular biology and discuss genomics and proteomics of cyanobacteria under abiotic stresses. Written by a team of global experts from 12 countries, this reference was created for phycologists, marine biologists, chemists, limnologists, botanists, and students of related fields"--